The effects of training at altitude on the functional capacity of the athletes - Ciucurel, C.; Georgescu, L.; Ciucurel, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim of the study was to determine the effects of the training at altitude, by physiological (cardio-respiratory) modifications point of view. Summary: A training stage at altitude represents a successful modality to increase the functional and the effortful capacity of the organism. The acquisitions must be exploited in maximum three weeks, because after this period the modifications are progressively reducing the amplitude. The results confirm the adaptation that human physiological systems make during exercise in response to exposure to stressful environments like altitude.